EXPERIENTIAL MARKETING AND EXPERIENTAL VALUE, HOW DOES IT IMPACT ON CONSUMER REPURCHASE INTENTIONS - Yanto, Beatrice Tan; Lindawati, Tuty; Pradana, Dominicus Wahyu (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2020)
Today's competition is very intens, with many restaurants, cafes and food court popping up so that competition arises from the side of sellers and consumers. Today's consumers are more likely to get bored so quickly that they will use all existing facilities such as information technology to get information about what they want to know. Marketers must have a positive strategy in experiential marketing to create a good experience for consumers. This study aims to determine the effect of experiential marketing on repurchase intention through experiential value for consumers of Pasa Rame Restaurant in Surabaya. Respondent samples used were 200 respondents who are the consumers of Pasa Rame Restaurant in Surabaya. Sampling of respondents using non probability sampling by purposive sampling. The data collection tool used is a questionnaire. The data analysis technique used is the Structural Equation Modelling using the Lisrel program.The results of this study state that experiential marketing has a positive and significant effect on experiential value, experiential marketing has a positive and significant effect on repurchase intention, experiential value has a positive and significant effect on repurchase intention and experiential marketing has a positive and significant effect on repurchase intention through experiential value for consumers of Pasa Rame Restaurant in Surabaya